Clinical utility of exhaled carbon monoxide in assessing preoperative smoking status and risks of postoperative morbidity after esophagectomy. Issue 9 (11th June 2018) - Yoshida, N; Baba, Y; Kuroda, D; Miyamoto, Y; Iwatsuki, M; Hiyoshi, Y; Ishimoto, T; Sawayama, H; Imamura, Y; Watanabe, M; Baba, H
Summary: Whereas smoking constitutes a significant risk factor for postesophagectomy morbidity, there is no reliable method to assess the smoking status of patients prior to the procedure. Since exhaled carbon monoxide (CO) is an indicator of recent smoking, this paper hypothesizes that this is a useful parameter in assessing current smoking status and may help predict morbidity following esophagectomy. Sixty-nine patients, who had undergone elective three-incision esophagectomy with two- or three-field lymphadenectomy for esophageal cancer, were prospectively studied between February 2015 and September 2017. At surgical admission, they were asked about their smoking history, their exhaled CO levels were evaluated, and they were grouped into three based on their CO levels. These were 0 parts per million (ppm), >0 and <7 ppm, and ≥7 ppm. Their postoperative morbidity was also assessed. Approximately 13.5% of the patients showed high levels of exhaled CO ≥ 7 ppm, despite preoperatively reporting smoking cessation for over a month. Morbidities of the Clavien–Dindo classification (CDc) ≥ II increased as exhaled CO levels increased and severe morbidity of CDc ≥ IIIb frequently was observed in patients with exhaled CO levels ≥7 ppm. The logistic regression analysis showed that exhaled CO level ≥7 ppm was an independent risk factor for severe postesophagectomy morbidity. Overall, the results of this study suggest that exhaled CO levels may be useful in estimating current smoking status and that it may also help give an estimation of the risk of postesophagectomy morbidity.